HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA TENTANG KESEHATAN REPRODUKSI DENGAN PERILAKU SEKSUAL PRANIKAH SISWA - Silvia Mona (Jurnal Penelitian Kesmasy, 2019)
This study aims to determine whether there is a relationship between knowledge and attitudes about reproductive health with premarital sexual behavior. The design of this study is an analytical survey with a cross-sectional approach. The population is 470 students and the total sample of this study is 82 students. Time to take in April-May 2018, the research instrument uses a questionnaire. Data analysis used the chi-square statistical test. The results of the study of knowledge were mostly 64 respondents (78.0%) with good knowledge, students who mostly had negative attitudes as much as 48 responses (41.5%), students who had premarital sexual behavior the majority were 66 respondent (80.5%). The conclusion of this study is that there is a relationship between attitudes and behaviors to increase knowledge, attitudes and behaviors about premarital sex.